What value of t makes the following equation true?
3(t−2)=−1
2 answers:
Answer:
t=
Step-by-step explanation:
3(t-2)=-1
3t-6=-1
3t-6+6=-1+6
3t=5
t=5/3
Answer:
5/3
Step-by-step explanation:
3(t - 2) = -1
3t - 6 = -1
3t = -1 + 6
3t = 5
t = 5/3 <==
lets check it..
3(5/3 - 2) = -1
3(5/3 - 6/3) = -1
3(-1/3) = -1
-3/3 = -1
-1 = -1 (correct)...it checks out
You might be interested in
Answer:
-48
Step-by-step explanation:
Multiply both sides of the equation by -8
-8(6) =
(-8)
-48 = w
Answer:
-16 and -1
Step-by-step explanation:
-16 *-1 = 16
-16+-1=-17
D the formula is v=(pie)(r)2(h)
Sorry I don’t have the right tools to do the equation right. But it’s D
Answer: Yes absolutely I come here for help alot and the answers are well thought out the majority for the time, I'd love to help if you want
Step-by-step explanation:
Step-by-step explanation:
Hope it helps.... that is how I did it